What’s Faith Got to Do with It? Religiosity Among Women Who Use Methamphetamine - Lutnick, Alexandra (2012)
Religiosity is not found to be consistently protective in mental health and substance use outcomes among illicit drug users. This study examines the association between religiosity, mental health and drug use among a community-recruited sample of women who use methamphetamine. The majority of the sample (74%) had high scores of religious faith. In multivariate analysis, those with high scores had higher odds of self-reporting a mental health diagnosis and of being psychologically dependent upon methamphetamine, and were less likely to report injection risk. Further examination of the role of religiosity in the lives of women who use methamphetamine is advised.